The Influence of Moderation Leverage on The Relationship Between Profitability and Firm Value: Empirical Study of Firms listed on the IDX, 2019-2021 period - Nuryaman Nuryaman; Eriana Kartadjumena; Dudi Abdul Hadi (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Capital market investors anticipate their investments will appreciate and progress in line with their investment objectives, specifically to enhance investor well-being. The investment value appreciates when the issuer's share price or firm value rises. Several variables can impact the value of a company, with profitability and leverage being two significant influences. Prior studies have presented empirical proof that a firm's profitability and leverage can impact its value. This study examines the moderating impact of leverage on the association between profitability and company value. The study utilized data from issuers listed on the Indonesia Stock Exchange from 2019 to 2021. At the time of this research, no existing studies examined the role of leverage as a moderating factor in the connection between profitability and company value. The data analysis revealed a strong positive correlation between profitability and firm valuation. High levels of leverage have a substantial detrimental impact on the value of a firm. The interaction variable of profitability and leverage has a negligible impact on the connection between profitability and firm value. The findings of this test indicate that leverage has a moderating effect that reduces the association between profitability and firm value. However, it is essential to note that leverage is not demonstrated to be a substantial moderating variable in this relationship.